TUTORIAL SUPPORT IN THE INFORMATION SPACE OF SCHOOLS - Glizburg, V.I.; Perevezentseva, O.N. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Informatizat͡s︡ii͡a︡ obrazovanii͡a, 2017)
The article deals with teachers and professional competence tyutorskoy, tutor support schools in the information space. The main requirements to the tutor support in the information space of schools, conditions of readiness of the teacher to tutor support schools in the information space. A theoretical analysis of the concept of information competence, tyutorskoy competence. It is noted that in thestructure of information competence must exist an element associated with the motivation, need and interest in the acquisition of knowledge and skills in the field of technical, software and information. Formulated key performance indicators definition of information competence of the tutor. The authors noted that information and work with it is in the modern educational and information space school mandatory components of pedagogical activity as a system.Analyzed and presented on the basis of the author’s experience of the possibility of using information and educational Moodle shell with tutor support positions in the information space of schools, sets out the basic elements and resources Moodle shell with a description of the implementation. In particular, the disclosed educational resources information and educational shell Moodle for remote support learning. The article describes a model developed by the author’s tutor support schools in the information space.